(untitled) (Research, Society and Development, 2023)
Objective: To describe the main noncommunicable chronic diseases (NCDs) prevalent in critically ill patients by Covid-19 in an ICU in the state of Rondônia. Methodology: Quantitative, descriptive, retrospective study conducted through the collection of secondary data in medical records of critically ill patients Covid-19 in an Intensive Care Unit in the year 2021. Results: There was a predominance of males, most of them aged > 45 to 60 years. Of these, 72% had at least one NCD, of which hypertension and diabetes mellitus were the most frequent (61.60%) and (33.90). As for the outcome, 71.5% died. Final Considerations: The findings of this study show the most susceptible profile to develop the severe form of Covid-19: male patients, aged over 60 years, affected by one or more NCDs. Therefore, the reduction of morbidity and mortality due to NCDs will be possible through the strengthening of primary health care in the promotion, prevention and rehabilitation of users with NCDs, emerges as a transformative proposal in the context of health care linked to PHC.